New di(heteroaryl)thioethers 1,3-diarylureas in the thieno[3,2-b]pyridine series as VEGFR2 tyrosine kinase inhibitors: docking, synthesis, enzymatic and cellular assays - Machado, Vera A. (2015)
Vascular Endothelial Growth Factor Receptor 2 (VEGFR2) is a tyrosine kinase receptor, expressed primarily in endothelial cells, and is activated by the specific binding of VEGF, produced and released by the tumor, to the VEGFR2 extracellular regulatory domain, undergoing autophosphorylation, triggering signaling pathways leading to endothelial cell proliferation towards the tumor [!].Small molecules may act as inhibitors by competing for the ATP-binding site of the VEGFR2 intracellular tyrosine kinase domain, thereby preventing the intracellular signaling that leads to angiogenesis [2]. Herein, we report the synthesis using rational design of new 1-aryl-3-[3-thieno[3,2-b]pyridin-7-ylthio)phenyl]ureas (la-c) as VEGFR2 tyrosine kinase inhibitors. The compounds presented, with the arylurea in the meta position to the thioether and with F or a Me group, showed very low !Cso values (11-28 nM) in enzymatic assays as predicted by molecular docking. To examine the activity of compounds 1 in endothelial cells, VEGF-stimulated (60 ng/mL) Human Umbilical Vein Endothelial Cells (HUVECs) were cultured in M199 medium in the absence (C) or presence of each compound at different concentrations. A remarkable reduction in the proliferation of HUVECs using the BrdU incorporation assay was observed for all compounds at I !JM, for compound la being observed a higher antiproliferative effect. Further studies are ongoing to examine whether these molecules affect the expression and activity of VEGFR2 and the signaling pathways, using western blotting assays. Given the established role of VEGFR2 in proliferation and migration of endothelial cells, these molecules are promising anti-angiogenic agents that can be used for therapeutic purposes in pathological conditions where angiogenesis is exacerbated, such as cancer.